2012
DOI: 10.1519/jsc.0b013e318270fcf0
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Rest Interval Length Manipulation of the First Upper-Body Resistance Exercise in Sequence on Acute Performance of Subsequent Exercises in Men and Women

Abstract: The purpose of the present study was to investigate the effects of manipulating rest interval (RI) length of the first upper-body exercise in sequence on subsequent resistance exercise performance. Twenty-two men and women with at least 1 year of resistance training experience performed resistance exercise protocols on 3 occasions in random order. Each protocol consisted of performing 4 barbell upper-body exercises in the same sequence (bench press, incline bench press, shoulder press, and bent-over row) for 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
3
1
1
Order By: Relevance
“…The pattern of repetitions per set and total repetitions were not different between sexes. Our results are different from those reported by other studies 13,14 Salvador et al 13 verified that women presented a performance of repetitions 24% lower than men.…”
Section: Discussioncontrasting
confidence: 99%
“…The pattern of repetitions per set and total repetitions were not different between sexes. Our results are different from those reported by other studies 13,14 Salvador et al 13 verified that women presented a performance of repetitions 24% lower than men.…”
Section: Discussioncontrasting
confidence: 99%
“…The obtained regression models make it possible to calculate the number of repetitions and rest interval to achieve the most rational load variant. These data supplement the results presented in the studies by Iermakov, Ivashchenko, Khudolii, and Chernenko (2020), Ivashchenko, Khudolii, Prusik, and Giovanis (2020) and form a methodology for studying training loads, which differs from the methods used in the studies by Arazi et al (2012), Ratamess et al (2012), Miranda et al (2010) in that research is conducted using an active 2 k FFE and materials are processed with the help of regression and discriminant analysis.…”
Section: Regression Equationsmentioning
confidence: 52%
“…In contrast to Arazi, et al (2012), Ratamess, et al (2012), Miranda, et al (2010, the study obtained data on the impact of orthogonal variants of alternation of strength exercises and rest intervals on the training effect of strength training loads. The paper confirmed that the efficiency of discriminant analysis increases when using 2 k FFE active experiments (Neimark, & Teklina, 2012;Tort-Martorell, 2009, 2012;.…”
Section: Discussionmentioning
confidence: 99%
“…The effective use of loads in physical education goes hand in hand with control and targeted regulation of rest intervals between exercises, their repetition and training in general, as well as with management of training effects of exercises (Ivashchenko, 2016;Bosenko, 2016;Veremeenko, 2019). The importance of studying rest intervals between strength exercises is indicated in papers by Arazi, Mirzaei, Sangdevini, and Abadi (2012), Ratamess, Chiarello, Sacco, Hoffman, Faigenbaum, Ross, and Kang (2012), Miranda, Simão, DosSantos-Vigário, DeSalles, Pacheco, and Willardson (2010). ISSN 1993-7989 (print).…”
Section: Introductionmentioning
confidence: 99%